Comparison of compressible and incompressible numerical methods in simulation of a cavitating jet through a poppet valve. Issue 1 (1st January 2019) - Yuan, Cong; Song, Jinchun; Liu, Minghe
ABSTRACT: The regime of compressible flow generally refers to the super/subsonic case. However, several remarkable cases with low Mach number could not be appropriately described with the incompressible method. It is a similar case for a cavitating jet inside a poppet valve. In order to comprehensively address the discrepancy between incompressible and compressible methods, both non-cavitating and cavitating cases are performed in experiment and calculation based on OpenFOAM. Experiment reveals a transition in flow pattern in both non-cavitating and cavitating flow. For example, for 0.7 mm openness and 30-degree poppet angle, transition happens at approximately 29 and 27 bar pressure drop for the two cases, respectively. In general, results from the compressible method exhibit better agreement with experiment regarding both flow performance and flow structure. By contrast, the incompressible method could not provide an accurate description for the transition process under the applied flow condition. A series of studies are carried out with emphasis on such discrepancy. Firstly, the deviation in flow performance is addressed based on velocity profile and turbulence level. Secondly, the disparity in flow structure is illustrated and the mechanism for cavitation inception is discussed, which combined provide an interpretation of the deficiency of the incompressible method. Thirdly, different inlet boundary conditions are applied, and the results confirm the independence of deficiency of the incompressible method for inlet fluctuation. Finally, a re-examination is proposed concerning traditional notion of compressible flow as well as the applicability of incompressible numerical method.